Galectin‐3 is associated with severe heart failure and death: A hospital‐based study in Chinese patients. (5th March 2020) - Wang, Na; Dang, Minyan; Zhang, Wenzhi; Lei, Yan; Liu, Zhaochuan
Abstract: Heart failure (HF) is a serious disease syndrome characterized by elevated pro‐inflammatory cytokines and inflammatory mediators presume to have significant contribution on disease progression. Galectins are carbohydrate‐binding proteins responsible of various physiological functions. Role of galectins in heart failure has been ill‐defined. In the present case‐controls study, 136 patients clinically diagnosed with heart failure and 125 healthy Chinese controls were recruited. Levels of galectins (Gal‐1, 3 and 9) and cytokines (IFN‐γ, IL‐17A, IL‐4 and TGF‐β) were quantified by ELISA. Increased levels of galectin‐1 and 3 was observed in HF patients and associated with clinical severity. In addition, pro‐inflammatory cytokines such as IFN‐γ and IL‐17A were increased in patients whereas, anti‐inflammatory TGFβ was decreased. Galectin‐3 was positively correlated with IFN‐γ, IL‐17A and inversely with TGF‐β. Furthermore, ROC curve analysis suggested galectin‐3 as a promising biomarker for diagnosis and HF and clinical severity. Interestingly, a two‐year follow‐up indicated significant association of elevated galectin‐3 with mortality due to HF. In conclusion, galectin‐3 associated with HF and clinical manifestations possibly by inducing pro‐inflammatory cytokines and could be a possible biomarker of HF and severe clinical conditions.